Advantages of “Soft Steroids” in the Treatment of Inflammatory Eye Diseases. Оverview - D. Yu. Maychuk; A. A. Tarkhanova (Oftalʹmologiâ, 2021)
The purpose to assess the benefits of using soft steroids in the treatment of inflammatory eye disorders according to literature data.Methods. The literature review concerning the administration of the gluco-corticosteroids and combination drugs based on gluco-corticosteroid for the treatment of inflammatory eye disorders. Both Russian and foreign sources for the 1980–2021 period were analyzed.The results. The combination drugs containing anti-infective drugs and gluco-corticosteroids are actively applied for the treatment of inflammatory eye disorders. That exerts joint ethiopathogenetic effect on the disorder. However, gluco-corticosteroid being a part of such drugs (predominantly dexamethasone) as often as not leads to ocular hypertension. In order to deal with this problem the so-called soft steroids (also classified as gluco-corticosteroids) were introduced. They lessen the possibility of the ocular hypertension and are marked by high efficiency and increased safety profile. One of the representatives of soft steroids is fluorometholone. There is a large evidential base in the modern literature that confirms much lesser influence of fluorometholone on ocular pressure if compared to dexamethasone. At the same time, dexamethasone has a higher anti-inflammatory activity, while on the other hand, its systemic immunosuppressive activity is lower. What is more, in terms of influence on the ocular surfaces, dexamethasone has an additional advantage which is causing mucin expression in conjuctival and corneal epithelium. The above mentioned merits of dexamethasone served as basis for its inclusion into the combination drug called Floas-T which is essentially the combination of tobramycin 0.3 % and fluorometholone 0.1 %. It is used in the treatment of inflammatory eye diseases and diseases of eye appendages, as well as for profylaxis of the diseases in the postoperative period.Conclusion. Combination drugs containing anti-infective components and gluco-corticosteroids seem to be highly promising for the treatment of inflammatory eye diseases. One of them worth highlighting is Floas-T classified as soft steroids containing tobramycin and fluorometholone. It compares to dexamethasone favourably in terms of efficiency, while contributing less to ocular hypertension.